The concepts of menopause. Part II – evolutionary and developmental approach - Bielawska-Batorowicz, Eleonora (Menopause Review/Przegląd Menopauzalny, 2005)
This paper continues to overview concepts of menopause. In the paper two approaches are presented: evolutionary and developmental. Evolutionary approach gives account on the role of menopause in human reproductive success and explains why menopause is a female phenomenon. The paper provides arguments regarding two main evolutionary hypotheses: grandmother hypothesis and altriciality-lifespan hypothesis. Additionally the arguments related to the role of menopause in preventing infanticide and encouraging continued investment by agnates are given. The developmental approach relates menopause to developmental stages in adulthood and also to most important developmental tasks. It is stressed that the most important tasks for midlife include the acceptance of biological changes.